Formulasi Nanoemulgel Peel Off Ekstrak Buah Stroberi (Fragaria x ananassa) dan Minyak Palmarosa (Cymbopogon martinii) Sebagai Antibakteri Propionibacterium acnes - Sundari, Pungky; Puspitasari, Dian; Nur Rahmawati, Aulia (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2024)
Acne is an inflammatory skin disorder that is mostly caused by Propionibacterium acnes. Secondary metabolites such as saponins, tannins, and flavonoids in strawberries and geraniol in Palmarosa oil can function as antibacterials. To produce a more durable product and increase the solubility of Palmarosa oil, a formula was developed in the form of a nanoemulgel peel-off mask because it is easy to apply to the skin, the active ingredient is quickly penetrated, and increases the stability of the active ingredient. The research aims to determine the effect of different concentrations of strawberry fruit extract on the physical properties and antibacterial activity of the test preparation against Propionibacterium acnes. The nanoemulgel peel-off mask was formulated in 3 different concentrations of strawberry fruit extract, namely F1 = 3%, F2 = 4%, and F3 = 5%. The nanoemulgel peel-off mask preparation was made by inserting nanoemulsion into the gel. The test evaluation included the % transmittance test, nanoemulsion type, pH, organoleptic, homogeneity, adhesion, spreadability, viscosity, drying time, and Propionibacterium acnes antibacterial activity test. The results showed that the difference in concentration of Strawberry fruit extract in the nanoemulgel peel off mask preparation had a significant effect on the results of pH, viscosity, spreadability, and adhesion tests, but did not have a significant effect on the results of the Propionibacterium acnes antibacterial activity test. The concentration of 5% Strawberry fruit extract in formula 3 had the best physical properties of the preparation and the greatest antibacterial activity of Propionibacterium acnes compared to other formulas with an inhibition zone value of 12.19 ± 0.70 mm.